1998
DOI: 10.1111/j.1479-828x.1998.tb02950.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Congenital Diaphragmatic Hernia

Abstract: Congenital diaphragmatic hernia (CDH) contributes significantly to perinatal morbidity and mortality. This retrospective study examines the experience of a major teaching hospital to establish survival rates and factors influencing outcome. Survival rates were found to relate closely to the stage at which the diagnosis was made and the presence of associated anomalies. Ultrasound diagnosis early in pregnancy is associated with a higher mortality rate than diagnosis made late in pregnancy or after delivery. Log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…MCA were identified in about 16 per 10,000 live births in metropolitan Atlanta from 1968 to 1989; however, 13% of the infants with MCA ascertained in metropolitan Atlanta in 1988–89 had identified chromosomal abnormalities [Khoury et al, 1991]. Infants with MCA usually require extensive and frequent medical care; their morbidity and mortality are substantially higher than that for infants with isolated anomalies [Putnam, 1979; Iuchtman et al, 1992; Engum et al, 1995; Moore et al, 1998; Heider et al, 2004]. Based on previous epidemiologic studies that have identified different risk factors for infants with isolated defects as compared with multiple major defects [Khoury et al, 1982a,b, 1989; Botto et al, 1996; Moore et al, 1997], we assume that the etiology for infants with MCA is different than that for infants with one isolated defect.…”
Section: Introductionmentioning
confidence: 99%
“…MCA were identified in about 16 per 10,000 live births in metropolitan Atlanta from 1968 to 1989; however, 13% of the infants with MCA ascertained in metropolitan Atlanta in 1988–89 had identified chromosomal abnormalities [Khoury et al, 1991]. Infants with MCA usually require extensive and frequent medical care; their morbidity and mortality are substantially higher than that for infants with isolated anomalies [Putnam, 1979; Iuchtman et al, 1992; Engum et al, 1995; Moore et al, 1998; Heider et al, 2004]. Based on previous epidemiologic studies that have identified different risk factors for infants with isolated defects as compared with multiple major defects [Khoury et al, 1982a,b, 1989; Botto et al, 1996; Moore et al, 1997], we assume that the etiology for infants with MCA is different than that for infants with one isolated defect.…”
Section: Introductionmentioning
confidence: 99%
“…1 The mortality rate for isolated CDH diagnosed before the 21st week has been reported as 45%. 2 Approximately half of all cases of CDH occur as isolated malformations, and, in these cases, brain development is assumed to be normal with neurodevelopmental outcome for these infants being viewed optimistically. For the remaining 50% of infants with a coexisting anomaly, approximately 7% will have anomalies of the central nervous system.…”
mentioning
confidence: 99%
“…In a German study of children with MMC, the sensitivity of prenatal ultrasound increased from 0 to 37% between 1982 and 1990 with a mean detection rate of 27% (18). Higher prenatal detection rates of CDH (53%-87%) have also been reported in recent population-based studies (9,19).…”
Section: Discussionmentioning
confidence: 88%